A double species 23Na and 87Rb Bose–Einstein condensate with tunable miscibility via an interspecies Feshbach resonance. (24th November 2015) - Wang, Fudong; Li, Xiaoke; Xiong, Dezhi; Wang, Dajun
Abstract: We have realized a dual-species Bose–Einstein condensate (BEC) of 23 Na and 87 Rb atoms and observed its immiscibility. Because of the favorable background intra- and inter-species scattering lengths, stable condensates can be obtained via efficient evaporative cooling and sympathetic cooling without the need for fine tuning of the interactions. Our system thus provides a clean platform for studying inter-species interactions–driven effects in superfluid mixtures. With a Feshbach resonance, we have successfully created double BECs with largely tunable inter-species interactions and studied the miscible–immiscible phase transition.